Medicinal plants in a changing climate: understanding the links between environmental stress and secondary metabolite synthesis - Jangpangi, Devesh; Patni, Babita; Chandola, Vaishali; Chandra, Sudeep (Frontiers in Plant Science, 2025)
Environmental stresses, including temperature extremes (cold and heat), elevated CO2, and ozone, significantly influence the production of plant secondary metabolites (PSMs). These environmental factors can lead to significant changes in the morphology, physiology, and biochemistry of plants. Natural resources, especially medicinal plants, have been used for centuries for their healing properties. PSMs, compounds with unique characteristics, often accumulate in response to stress, playing a crucial role in plant adaptation and stress tolerance. While environmental variables like temperature, light, water availability, humidity, CO2, and mineral nutrition are known to impact plant development and PSM synthesis, research on the effects of climate change on medicinal plants is limited compared to other commercial crops. This review examines the impact of various environmental factors on PSM synthesis in medicinal plants and identifies key knowledge gaps. We highlight the need for further research in this area and suggest potential directions for future studies to better understand and potentially manipulate the relationship between climate change, environmental stress, and the production of therapeutically valuable PSMs.